Revisiting Aspectos de relações públicas - Alves, Fabianna Pereira Bluhm; Amoêdo, Sebastião (Organicom, 2009)
This text has the aim of revisiting the book Aspectos de relações públicas (Aspects of public relations), written by Sylla Chaves (1966), which is considered to be one of the classics of the Public Relations theory, adding thoughts updated by the eminent author in an interview designed and developed by the authors of this article. Initially, together with the interview, it deals with the definition of Public Relations, then goes on to the issue of professional of the area area, through using subjects like public relations and “enlightened selfishness”. With the death of Sylla Chaves in May 2009, this work paper becomes a tribute to his lifetime work.